Critical Evaluation of Quasi-Judicial Institutions in the Indonesian Legal System - Handojo Dhanudibroto; Ina Heliany (Eduvest - Journal of Universal Studies, 2026)
Background: Quasi-judicial institutions are new institutions that emerged after the 1998 reforms as auxiliary organs tasked with resolving specific legal disputes. After that year, the government began establishing several quasi-judicial institutions such as the Consumer Dispute Resolution Agency, the National Commission on Human Rights, the Business Competition Supervisory Commission, the Ombudsman, the Professional Disciplinary Council, and several other institutions. Objective: This study aims to examine the position of quasi-judicial institutions in the Indonesian legal system and the obstacles they face within the existing legal system. Methods: The research methodology used was normative juridical, where the author conducts a literature review of legal theory, legislation, and existing quasi-judicial institutions to clarify their position and explain their uses and obstacles. Results: This was done with the aim of ensuring that specific legal disputes can obtain appropriate and beneficial justice for the disputing parties through a fast and efficient process. In some quasi-judicial institutions, decisions from these institutions can even contribute to making legally binding decisions that can be considered by judges in general courts or provide recommendations on whether a legal dispute can be forwarded to general courts or not. However, historically, some of these institutions' decisions have experienced inconsistencies with those of general courts. Conclusion: Therefore, in this paper, the author attempts to provide suggestions on how to address potential inconsistencies between the results of decisions and those of general courts.